2012
DOI: 10.1042/bj20121061
|View full text |Cite
|
Sign up to set email alerts
|

The activation loop of PKA catalytic isoforms is differentially phosphorylated by Pkh protein kinases in Saccharomyces cerevisiae

Abstract: PDK1 (phosphoinositide-dependent protein kinase 1) phosphorylates and activates PKA (cAMP-dependent protein kinase) in vitro. Docking of the HM (hydrophobic motif) in the C-terminal tail of the PKA catalytic subunits on to the PIF (PDK1-interacting fragment) pocket of PDK1 is a critical step in this activation process. However, PDK1 regulation of PKA in vivo remains controversial. Saccharomyces cerevisiae contains three PKA catalytic subunits, TPK1, TPK2 and TPK3. We demonstrate that Pkh [PKB (protein kinase B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Our results suggest that their regulation by Bcy1 is also partly specific. For instance, our assay identified PKH1 as a PKA2-specific candidate, in agreement with evidence that Pkh1 preferentially phosphorylates Tpk2 over its paralogs (27). Moreover, our results follow patterns of compartmentalized activation and inactivation (Fig.…”
Section: Resultssupporting
confidence: 75%
“…Our results suggest that their regulation by Bcy1 is also partly specific. For instance, our assay identified PKH1 as a PKA2-specific candidate, in agreement with evidence that Pkh1 preferentially phosphorylates Tpk2 over its paralogs (27). Moreover, our results follow patterns of compartmentalized activation and inactivation (Fig.…”
Section: Resultssupporting
confidence: 75%
“…Several post-translational modifications on regulatory and catalytic subunits of yeast PKA affect its nuclear-cytoplasmic localization [55][56][57]. The transport mechanism of PKA subunits through nuclear membrane has not been previously characterized.…”
Section: Mechanism Of Nuclear Accumulation Of Pka In Response To Osmomentioning
confidence: 99%
“…Tpk1 protein showed similar levels of pThr 241 signal independently of the presence of a negative charge on Ser 179 , suggesting that the phosphorylation status of Ser 179 did not affect the phosphorylation of Thr 241 by Pkh1 kinase. Secondly, we analysed the phosphorylation state of Ser 179 in a pkh1 ts pkh2 pkh3 strain ( Figure 4D, right-hand panel) in which we have already shown that pThr 241 is decreased [6]. We found an increased pSer 179 signal in Tpk1 purified from the Pkh1 inactive strain.…”
Section: Tpk1 Phosphorylation On Ser 179 Occurs During the Transitionmentioning
confidence: 92%
“…This phosphorylation was independent of nitrogen or glucose availability [5]. We have shown that Pkh1 inactivation reduces the interaction between Tpk1 and the regulatory subunit Bcy1 without affecting the specific kinase activity [6]. To assess the interrelationship between Thr 241 and Ser 179 phosphorylation, we first evaluated the phosphorylation state of Thr 241 in Tpk1, tpk1 S179A and tpk1 S179D ( Figure 4D, left-hand panel).…”
Section: Tpk1 Phosphorylation On Ser 179 Occurs During the Transitionmentioning
confidence: 98%
See 1 more Smart Citation